2021
DOI: 10.3389/fpls.2021.733236
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Water Potential Induced by Salt, Alkali, and Drought Stresses Has Different Impacts on the Seedling of Hordeum jubatum: From Growth, Photosynthesis, and Chlorophyll Fluorescence

Abstract: Hordeum jubatum is a halophyte ornamental plant wildly distributed in the Northeast of China, where the low water potential induced by various abiotic stresses is a major factor limiting plant growth and development. However, little is known about the comparative effects of salt, alkali, and drought stresses at uniform water potential on the plants. In the present study, the growth, gas exchange parameters, photosynthetic pigments, and chlorophyll fluorescence in the seedlings of H. jubatum under three low wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…A fast and significant decline in the photosynthetic parameters (P n , gs, C i , T r , and F v /F m ) and chlorophyll content occurred in both diploids and tetraploids under drought stress ( Figure 5 ). Consistent with our results, Shi et al (2021) reported that photosynthetic parameters (P n , gs, C i , and T r ) and water potential were all decreased in Hordeum jubatum seedlings under drought stress. In addition, Zhang et al (2021) reported that drought stress caused declines in the chlorophyll content, P n and Gs values, and F v /F m ratio in Atractylodes lancea .…”
Section: Discussionsupporting
confidence: 92%
“…A fast and significant decline in the photosynthetic parameters (P n , gs, C i , T r , and F v /F m ) and chlorophyll content occurred in both diploids and tetraploids under drought stress ( Figure 5 ). Consistent with our results, Shi et al (2021) reported that photosynthetic parameters (P n , gs, C i , and T r ) and water potential were all decreased in Hordeum jubatum seedlings under drought stress. In addition, Zhang et al (2021) reported that drought stress caused declines in the chlorophyll content, P n and Gs values, and F v /F m ratio in Atractylodes lancea .…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that saline-alkali stress reduced the water content of oat leaves, resulting in the yellowing of some leaves, and chlorophyll a, chlorophyll b, and total chlorophyll content was significantly decreased. Similar findings have been reported in studies on sorghum [11] and ryegrass [36]. Numerous studies have shown that MT increases photosynthetic pigment content in plant leaves under abiotic stress, delays leaf senescence, promotes light energy uptake and conversion, and ensures the accumulation of plant organic matter [37][38][39].…”
Section: Mt Treatment Effects On Photosynthetic Physiologysupporting
confidence: 82%
“…According to Urban et al [56], while substantial decreases in F v /F m and ΦPSII values are indicators of photodamage, small reductions in these parameters can be interpreted in terms of photoprotection. In the present study, the minor decreases in F v /F m (−2%) and ΦPSII (−4%) under water deficit in WATER, NPGA 3 , and NP treatments could be associated with the induction of protective mechanisms against stress [57].…”
Section: Methodsmentioning
confidence: 47%